2021
DOI: 10.1111/tbed.14041
|View full text |Cite
|
Sign up to set email alerts
|

Prospective surveillance study in a 1,400‐bed university hospital: COVID‐19 exposure at home was the main risk factor for SARS‐CoV‐2 point seroprevalence among hospital staff

Abstract: The Co‐HCW study is a prospective cohort study among hospital staff, including healthcare workers (HCWs) and administration staff, at the Jena University Hospital (JUH), Germany. The objectives of this study were to assess SARS‐CoV‐2 IgG seroprevalence, individual exposure risk factors and compliance of HCWs to wear personal protective equipment (PPE). After the first nosocomial COVID‐19 outbreak at JUH, mandatory masking was implemented on 20th March 2020. We evaluated point seroprevalence using two IgG detec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 50 publications
4
27
1
2
Order By: Relevance
“…Looking at the risk to acquire the SARS-CoV-2 infection privately or at work, we may assume that the participating hospitals were probably no places of infectious spread to employees in the first pandemic wave. Some studies on HCWs in Germany also differentiated between seroprevalence rates according to the risk at work [14,21], and investigated highrisk group HCWs on ICU, the COVID-19 ward and emergency department [19,22,23,31]. All these studies found a low seroprevalence up to 4.36% [18] in the first pandemic wave.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the risk to acquire the SARS-CoV-2 infection privately or at work, we may assume that the participating hospitals were probably no places of infectious spread to employees in the first pandemic wave. Some studies on HCWs in Germany also differentiated between seroprevalence rates according to the risk at work [14,21], and investigated highrisk group HCWs on ICU, the COVID-19 ward and emergency department [19,22,23,31]. All these studies found a low seroprevalence up to 4.36% [18] in the first pandemic wave.…”
Section: Discussionmentioning
confidence: 99%
“…Data from German HCWs are available from a variety of hospitals, but nearly all published data focus on the first pandemic wave [14][15][16][17][18][19][20] (Table 1). Two hospitals reported data until December 2020 [21,22], but no information for HCWs in Germany is available for the year 2021 so far.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-four-item Wisconsin Upper Respiratory System Survey (WURSS-24), which is a valid instrument (Barrett et al, 2005) to evaluate the illness-specific quality of life and the negative impact of acute Upper Respiratory Tract Infection symptoms (URTIs), has been used for assessment in COVID-19 patients (Bahrs et al, 2021) (Holmes, Macfarlane, Macfarlane, & Hubbard, 2001). All patients were asked whether or not they experienced these symptoms during the study period.…”
Section: Questionnairesmentioning
confidence: 99%
“…Während einige Studien die Seroprävalenz als Punktprävalenz bestimmt haben [ 1 , 8 ], zeigt diese Studie die Seroprävalenz über den Zeitraum der ersten und zweiten Pandemiewelle in Deutschland bis zum Beginn von Impfungen gegen SARS-CoV‑2 auf. In einer kürzlich publizierten prospektiven Kohortenstudie [ 3 ] mit 17.383 Teilnehmern von Juni bis Dezember 2020 fand sich eine höhere Inzidenzdichte von 57,3 Infektionen pro 100.000 Personentage im Vergleich zu dieser Studie (16,8 Infektionen pro 100.000 Personentage).…”
Section: Diskussionunclassified